2004
DOI: 10.1002/chin.200440012
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Visible Photoluminescence from ZnO Thin Films Through Mg‐Doping and Annealing.

Abstract: Luminescence D 6540 Tunable Visible Photoluminescence from ZnO Thin Films Through Mg-Doping and Annealing. -Visible photoluminescence from ZnO thin films is tunable in a wide wavelength range. Mg-doped ZnO films, annealed in H2/N2 and air, exhibit strong blue and orange emissions upon UV excitation, respectively. Yellow photoluminescence is observed in (Al, Li)-doped ZnO films. -(FUJIHARA*, S.; OGAWA, Y.; KASAI, A.; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…The visible PL emission (PL VIS ) with a wide FWHM is observed in the pure ZnO thin film. Similar results have been reported and shown this PL VIS is from the contribution of the native defects in ZnO, which can be efficiently controlled by various post-annealing methods [15,16]. Hence, the increased PL VIS in sample FA-1000 can be mainly inferred from the higher native defect density in ZnO matrix since it has a smaller crystalline size than that in pure ZnO thin film.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The visible PL emission (PL VIS ) with a wide FWHM is observed in the pure ZnO thin film. Similar results have been reported and shown this PL VIS is from the contribution of the native defects in ZnO, which can be efficiently controlled by various post-annealing methods [15,16]. Hence, the increased PL VIS in sample FA-1000 can be mainly inferred from the higher native defect density in ZnO matrix since it has a smaller crystalline size than that in pure ZnO thin film.…”
Section: Resultssupporting
confidence: 84%
“…Hence, the increased PL VIS in sample FA-1000 can be mainly inferred from the higher native defect density in ZnO matrix since it has a smaller crystalline size than that in pure ZnO thin film. In addition to the increased PL VIS , the PL spectrum accompanies increased near-infrared emission (PL NIR ) and an unusual peak (PL unusual ) located at 685 nm (1.81 eV), which have not been reported in pure or doped ZnO materials [15,16], for sample FA-1000. This PL unusual may be contributed from the nc-Si QDs embedded in the ZnO matrix with wide bandgap.…”
Section: Resultsmentioning
confidence: 84%
“…However, after annealing, the yellow emission is improved with a blue shift towards a wavelength of 594 nm. Fujihara et al [47] and Chen et al [48] have also reported a blue shift in their studies.…”
Section: Photoluminescence Studies Of Filmsmentioning
confidence: 81%
“…With the content of the CPAN increasement, both the UV and visible emissions of the Ag/ZnO photocatalyst rapidly decrease. The decrease of the emission for the ZnO/CPAN nanocomposites can be ascribed to the electron trapping and transmitting effect of CPAN, which acts as electron acceptor, thus hindering the recombination of charge carriers on ZnO . The electron trapping and transmitting effect of CPAN is favorable for the improvement of the photocatalytic activity of ZnO due to the enhancement of the separation efficiency of photogenerated electrons and holes .…”
Section: Resultsmentioning
confidence: 99%